2019
DOI: 10.1111/his.13850
|View full text |Cite
|
Sign up to set email alerts
|

Histological ageing of fractures in infants: a practical algorithm for assessing infants suspected of accidental or non‐accidental injury

Abstract: Aims This study is the first to systematically document histological features of fractures of known age in infants (≦12 months). It has been used to develop a tabulated database specifically to guide histopathologists to age fractures in children considered to have suffered accidental or non‐accidental injury ( NAI ). Currently in the United Kingdom there are insufficient pathologists with experience in histological ageing of fractures to meet the medicolegal need for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
(57 reference statements)
0
18
0
Order By: Relevance
“…He was therefore of the view that these findings should not be used to discriminate between true invivo injury and peri-mortem injury. Another key observation in James' study is the demonstration of 'empty lacunae'which had been previously been considered by some authors to represent a marker of vitality at the time of injury, implying osteocyte necrosis 8 in the cortical/trabecular bone at the edge of CPR-related fractures. As such, it is concluded that the observation of 'empty lacunae' is therefore not necessarily a feature indicative of the ante-mortem nature of a fracture.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…He was therefore of the view that these findings should not be used to discriminate between true invivo injury and peri-mortem injury. Another key observation in James' study is the demonstration of 'empty lacunae'which had been previously been considered by some authors to represent a marker of vitality at the time of injury, implying osteocyte necrosis 8 in the cortical/trabecular bone at the edge of CPR-related fractures. As such, it is concluded that the observation of 'empty lacunae' is therefore not necessarily a feature indicative of the ante-mortem nature of a fracture.…”
mentioning
confidence: 90%
“…The forensic pathologist needs to be able to assist the Court where possible by narrowing the time‐period when a fracture was sustained, as well as the probable mechanism of causation. By carefully studying the histological findings in bone the age of fractures can be determined within a time‐frame, 8 as well as the presence or absence of metabolic changes that may have a bearing on the nature of the force needed to produce a fracture 2–4 …”
mentioning
confidence: 99%
“…Marks et al (2009) have also suggested that it may be possible to use the histological measurement of SPNBF to estimate TSI. Naqvi, Raynor, and Freemont (2019) correlated the presence of histological features with known date of injury based on a collection of 169 fracture samples from 52 infants collected over a 32-year period. Table 2 provides the histological features by observed time interval, although some features varied in timing based on fracture location (Naqvi et al, 2019).…”
Section: Histological Analysismentioning
confidence: 99%
“…Rib cut axially and stained with hematoxylin-eosin (H&E). Arrow indicating ossifying soft callus on the pleural surface of the rib (L = lateral; M = medial) T A B L E 2 Correlation of histological characteristics with known time since injury according toNaqvi et al (2019) Note: h = hours; d = days.…”
mentioning
confidence: 99%
“…In an article in this journal 10 in the context of infant fracture histology, the claim was made that haemorrhage into the fracture gap, periosteum or marrow cavity may be used to differentiate a fracture occurring in life from one occurring during CPR or after death, and that the absence of osteocyte nuclei in the bone margins of the fracture indicates osteocyte necrosis, and the passage of at least 1 h between fracture and death. It is of concern that none of the cases described in that article sustained fractures at the time of death or after death; the article did not provide objective evidence of its claims that: ‘it is generally accepted that postmortem fractures (including CPR‐induced) do not bleed significantly’; ‘our experience is that [osteocyte necrosis in cortical/trabecular bone at fracture edges] is never seen in postmortem fractures’; or that ‘we have redefined antemortem haemorrhage to include significant medullary or periosteal haemorrhage with or without RBC in the cortical fracture line’ 10 . These claims were made without objective validation from cases or the medical literature, and no reference was made to the body of literature conflicting with the authors’ claims.…”
Section: Introductionmentioning
confidence: 99%